2015
DOI: 10.5194/acp-15-7703-2015
|View full text |Cite
|
Sign up to set email alerts
|

Climate-forced air-quality modeling at the urban scale: sensitivity to model resolution, emissions and meteorology

Abstract: Abstract. While previous research helped to identify and prioritize the sources of error in air-quality modeling due to anthropogenic emissions and spatial scale effects, our knowledge is limited on how these uncertainties affect climateforced air-quality assessments. Using as reference a 10-year model simulation over the greater Paris (France) area at 4 km resolution and anthropogenic emissions from a 1 km resolution bottom-up inventory, through several tests we estimate the sensitivity of modeled ozone and P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 77 publications
3
43
0
Order By: Relevance
“…PM 2.5 concentrations have also been found to be sensitive to the model horizontal resolution (Arunachalam et al, 2011;Punger and West, 2013;Markakis et al, 2015;Neal et al, 2017). In the US, Punger and West (2013) found populationweighted annual mean PM 2.5 concentrations to be 6 % higher at 36 km compared to 12 km, but 27 % lower when simulated at 408 km compared to 12 km.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…PM 2.5 concentrations have also been found to be sensitive to the model horizontal resolution (Arunachalam et al, 2011;Punger and West, 2013;Markakis et al, 2015;Neal et al, 2017). In the US, Punger and West (2013) found populationweighted annual mean PM 2.5 concentrations to be 6 % higher at 36 km compared to 12 km, but 27 % lower when simulated at 408 km compared to 12 km.…”
Section: Introductionmentioning
confidence: 95%
“…Investigating the impact of increasing model horizontal resolution from 48 to 6 km on O 3 concentrations in Paris, Valari and Menut (2008) found modelled surface O 3 to be more sensitive to the resolution of input emissions than to meteorology. A number of other studies note the sensitivity of simulated O 3 to simulated nitrogen oxide (NO x ) concentrations that determine the extent of titration of O 3 by nitrogen monoxide (NO) (Stock et al, 2014;Markakis et al, 2015;Schaap et al, 2015). Furthermore, Stock et al (2014) found the impact of spatial resolution (150 km vs. 40 km) on simulated O 3 concentrations to vary with season across Europe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On regional scales, many studies focused on European urban centers, especially those in the Mediterranean region (e.g. Im et al, 2011a, b;Escudero et al, 2014;Finardi et al, 2014), but also covering London and the Ruhr area (Hodnebrog et al, 2011), or Paris (Skyllakou et al, 2014Markakis et al, 2015). The importance of multi-model modeling approach for investigating the megacities impact on air quality and climate was analyzed in detail by Baklanov et al (2010) in the framework of the European FP7 project MEGAPOLI.…”
mentioning
confidence: 99%
“…Therefore, we have proposed to conduct continuous, 10-year long simulations which decreases the uncertainty originating in the driving meteorological conditions. This choice was preferred also by Katragkou et al (2010) and Zanis et al (2011) or Markakis et al (2015). (3) Most of the above-listed regional studies focused on only one or two megacities (and their impact).…”
mentioning
confidence: 99%